1987
DOI: 10.1002/nur.4770100606
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intensity controlled aerobic dance exercise on aerobic capacity of middle‐aged, overweight women

Abstract: The purpose of this study was to determine the effect of intensity controlled exercise on the aerobic capacity of overweight, middle-aged women. Thirty-eight moderately overweight women, ages 35-57, participated in a 16-week dance-exercise program. Random assignment was made to an experimental group (n = 20) in which intensity of exercise was controlled and prescribed, and a control group (n = 18) in which exercise was of an intensity typical to commercial aerobic classes. Prior to the onset of training, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
2
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 16 publications
1
35
2
2
Order By: Relevance
“…These improvements in maximal and submaximal aerobic power are in agreement with previous studies using aerobic dance training for non-obese people (Blessing et al, 1987;Dowdy et al, 1985;Parker et al, 1989;Walberg, 1989;Williams and Morton, 1986;Willford et al, 1988). Gillett and Eisenman (1987) reported a rise of 41% in maximal aerobic power which surpassed what had been reported in other training studies. However, the length of the training period was longer than in other investigations (16 weeks vs 10 to 12 weeks).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…These improvements in maximal and submaximal aerobic power are in agreement with previous studies using aerobic dance training for non-obese people (Blessing et al, 1987;Dowdy et al, 1985;Parker et al, 1989;Walberg, 1989;Williams and Morton, 1986;Willford et al, 1988). Gillett and Eisenman (1987) reported a rise of 41% in maximal aerobic power which surpassed what had been reported in other training studies. However, the length of the training period was longer than in other investigations (16 weeks vs 10 to 12 weeks).…”
Section: Discussioncontrasting
confidence: 53%
“…However, the length of the training period was longer than in other investigations (16 weeks vs 10 to 12 weeks). Several investigators, who used 3-d/wk training regimen, have demonstrated significant improvements in maximal aerobic power following several weeks of dance exercise (Gillett and Eisenman, 1987;Moore et al, 1988;Williford et al, 1989). However, it seems that for women previously trained with traditional high impact aerobic dance, low impact dance may not be sufficiently demanding as a training alternative to maintain maximal aerobic power.…”
Section: Discussionmentioning
confidence: 99%
“…The items were derived from previous work of the principal investigator concerning the responses of older and middle-aged women to exercise programs (Gillett, 1988(Gillett, , 1993Gillett & Eisenman, 1987). For each item, the respondent rated how important that facet of exercise was for her on a scale from 1 (not at all important) to 5 (very important).…”
Section: Methodsmentioning
confidence: 99%
“…Clapp and Little 1994;Thomsen and Ballor 1991) have shown that the intensity level of performance of the instructor and the participants dier dramatically during aerobics classes, and that the physiological responses to exercise are individual. Gillett and Eisenman (1987) emphasized the importance of tailoring the intensity of the exercise to the individual and concluded that changes in cardiovascular ®tness in overweight women are greater when the exercise intensity is tailored to their ages and level of ®tness. According to Hawley et al (1990) instructors tend to create separate exercise routines at low and higher intensity levels.…”
Section: Introductionmentioning
confidence: 99%